2011
DOI: 10.1158/1078-0432.ccr-10-1300
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of Colorectal Cancer Biomarkers Identified from Bioinformatics Analysis of Public Expression Data

Abstract: Purpose: Identification of novel biomarkers of cancer is important for improved diagnosis, prognosis, and therapeutic intervention. This study aimed to identify marker genes of colorectal cancer (CRC) by combining bioinformatics analysis of gene expression data and validation experiments using patient samples and to examine the potential connection between validated markers and the established oncogenes such as c-Myc and K-ras.Experimental Design: Publicly available data from GenBank and Oncomine were meta-ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 32 publications
3
64
0
Order By: Relevance
“…CKS2 expression was also correlated with tumor size and differentiation. The reason for the results differing from Jung et al (14) may be due to the smaller number of patients from stage ⅱ in the latter. (17) first reported that CKS2 expression is strongly correlated with the progression of human BC.…”
Section: Cks2 Is Highly Expressed In Malignant Tumorsmentioning
confidence: 62%
See 1 more Smart Citation
“…CKS2 expression was also correlated with tumor size and differentiation. The reason for the results differing from Jung et al (14) may be due to the smaller number of patients from stage ⅱ in the latter. (17) first reported that CKS2 expression is strongly correlated with the progression of human BC.…”
Section: Cks2 Is Highly Expressed In Malignant Tumorsmentioning
confidence: 62%
“…In another study by Shen et al (29), the same results were exhibited in cholangiocarcinoma, and CKS2 overexpression was associated with poor differentiation. (14) studied the correlation between the CKS2 gene expression level and clinical characteristics in CRC tissues. The analysis of variance statistical test was used and the results showed that a high level of CKS2 expression was associated with early tumor stage.…”
Section: Cks2 Is Highly Expressed In Malignant Tumorsmentioning
confidence: 99%
“…It has been reported that the copy number of ECT2-located 3q26 frequently increases in several cancers including head and neck, lung and cervical cancer, suggesting that a genomic imbalance may contribute to the upregulation of ECT2 in OS (10,11). ECT2 has been considered to play an oncogenic role in several malignant tumors, including ovarian cancer, retinoblastoma, pancreatic ductal adenocarcinoma, cervical and colorectal cancers, oral squamous cell carcinoma, as well as OS (9,(12)(13)(14)(15)(16)(17). In the present study, it was shown that the expression of ECT2 was significantly upregulated in OS tissues when compared with that in normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ECT2 upregulation in other cancers has been widely demonstrated (9,(12)(13)(14)(15)(16)(17); however, these studies mainly focused on its effect on cell cycle progression. For instance, Iyoda et al observed that ECT2 was notably upregulated in oral squamous cell carcinoma, and that the inhibition of ECT2 caused cell cycle arrest at the G1 phase, accompanied by the upregulation of the cyclin-dependent kinase (CDK) interacting protein/kinase inhibitory protein family of CDK inhibitors, as well as downregulation of cyclin D1, cyclin E and CDK4 (17).…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study suggested that p42.3 is involved in cell cycle regulation and tumorigenesis and is expressed at significantly higher mRNA levels in many other cancer cells including human melanoma. [7][8][9][10] We have observed that p42.3 is also expressed at higher levels in human melanoma than in nevus (data not shown). Thus differential expression of p42.3 could not only be used to recognize The p42.3 gene was recently identified and characterized as having tumor-specific and mitosis phase-dependent expression in many types of cancer.…”
Section: Introductionmentioning
confidence: 79%